Distribution Characteristics, Regional Differences and Spatial Convergence of the Water-Energy-Land-Food Nexus: A Case Study of China - Qiangyi Li; Lan Yang; Fangxin Jiang; Yangqing Liu; Chenyang Guo; Shuya Han (Land, 2022)
Land use change affects the supply and demand of water, energy and food and the integration of land elements into the common water-energy-food (WEF) nexus, which is an effective way to strictly adhere to the bottom line of natural resources. First, this study used the entropy method and coupling coordination model to measure the coupling coordination degree of the water-energy-land-food (WELF) nexus in 30 provinces in China during the period of 2006–2019. Then, the regional differences and distribution dynamics were examined with the Dagum Gini coefficient and Kernel density estimation, respectively. Finally, the spatial correlation was analyzed using the global Moran’s I, and a spatial β convergence model was constructed to empirically test its spatial β convergence characteristics. The results show that the coupling coordination degree of the WELF nexus in most of the provinces was at the stage of barely coordinated, with a decreasing trend; the intensity of transvariation was the main source of regional differences in the coupling coordination degree of the WELF nexus, followed by intra-regional differences, while inter-regional differences were small. The national, eastern and central regions had a slight gradient effect, showing regional dispersion characteristics, albeit less obvious; there was a spatial absolute-β convergence and spatial conditional-β convergence nationally and in the three regions. On this basis, policy recommendations were made to realize the synergistic development of land planning, water resources allocation, energy utilization, and food production and to balance regional differences in resources.